Heparineless off‐pump coronary artery bypass in a patient with gunshot wound to chest and heart. Issue 7 (18th June 2019) - Brozzi, Nicolas A.; Cifuentes, Renzo O.; Saba, Isabela C.; Lineen, Edward B.; Loebe, Matthias; Ghodsizad, Ali; Salerno, Thomas A.
Abstract: Objectives: Administration of heparin is standard in coronary artery bypass grafting (CABG) with or without cardiopulmonary bypass (OPCABG). In some circumstances, the risk of heparinization may outweigh its benefits, and there is scarce literature on how to proceed in these cases. We describe the technique used for OPCABG without heparin. Methods: We report the case of a patient with a gunshot wound to the chest resulting in multiple lung lacerations and transection of the proximal left anterior descending coronary artery (LAD) leading to hemorrhagic shock with tamponade, and cardiogenic shock due to myocardial ischemia who received OPCABG without heparin. Results: A 23‐year‐old patient suffered multiple gunshot wounds to the chest and was admitted in shock with massive left hemothorax. Emergency left thoracotomy revealed multiple lung lacerations and transection of the proximal left anterior coronary artery. The patient presented acute myocardial ischemia and progressed to cardiogenic shock requiring insertion of intra‐aortic balloon pump (IABP) to try to support hemodynamics. OPCABG with a segment of reversed saphenous vein graft to the LAD coronary artery was performed using standard techniques but without heparinization. The graft was flushed with normal saline before completing both anastomosis. Myocardial ischemic changes reversed, and the patient stabilized immediately after completing OPCABG, allowing to wean off IABP in the operating room. Postoperative recovery was unremarkable, and the patient was discharged home on postoperative day 9. Conclusion: Benefits of OPCABG include decreased bleeding and lower requirement of blood transfusions. This experience shows that OPCABG can be performed without systemic heparinization in selected cases.